Family Relationship Among High School Students In Relation to Their Emotional Intelligence: Exploring the Impact of Parental Acceptance on Emotional Intelligence (Journal of Advances and Scholarly Researches in Allied Education, 2012)
This study made an attempt to studyfamily relationships among high school students in relation to their emotionalintelligence. The sample of the present study comprised 300 high schoolstudents of Panipat district of Haryana state. Family Relationship Inventorydeveloped and standardized by Sherry and Sinha and emotional Intelligence scaledeveloped and standardized by Hyde, Pethe and Dhar were used. The findingsshowed that significant relationship was found between emotional intelligenceand parental acceptance. Insignificant but negative relationship was foundbetween emotional intelligence and parental concentration. Significant butnegative relationship was found between emotional intelligence and parentalavoidance.